Visual Inspection and Toothbrush Care: A Mother-Baby Paired Cross-Sectional Study - Yuri Jivago Silva Ribeiro; Iza Teixeira Alves Peixoto; Raquel Assed Bezerra Segato; Paulo Nelson-Filho; Alexandra Mussolino de Queiroz; Francisco Wanderley Garcia Paula-Silva (Association of Support to Oral Health Research (APESB), 2022)
Objective: To evaluate the physical conditions and presence of residues of toothbrushes used by mothers and their babies and mothers' knowledge about toothbrush care. Material and Methods: This was a cross-sectional study comprising a convenience sample represented by 60 mother-baby pairs. The mothers answered a questionnaire to evaluate their knowledge of toothbrush care. A calibrated dentist performed a visual inspection of the toothbrushes. Statistical analysis was performed using the chi-square and Fisher's exact tests, with a significance level of 5%. Results: It was found that 82% of the mothers had never received instructions regarding the care of toothbrushes after use (p=0.024). Most of them believed that their toothbrushes (70%) and their children's toothbrushes (88%) were in good condition to use (p=0.043). However, most mother's toothbrushes presented an unacceptable deformity of the bristles (65%) and the presence of residues (60%). In addition, babies' toothbrushes also presented unacceptable deformities of the bristles (52%) and residues (55%). There was an association between the lack of instructions received by the mother and the presence of deformity and residues on the mother's toothbrush bristles (p=0.037 and p=0.003, respectively). Conclusion: Most mothers had never received instructions regarding toothbrush care, which is reflected in the condition of their and their baby's toothbrushes, which presented unacceptable physical conditions concerning deformation and presence of residues.